Expectations of access to debt finance for SMEs in times of uncertainty. (2nd November 2022) - Calabrese, Raffaella; Degl'Innocenti, Marta; Zhou, Si
ABSTRACT: This articles examines small and medium enterprises' (SMEs) expectations of access to debt finance in times of uncertainty. In particular, we studied whether relationship lending affects British SMEs' concerns about future access to debt finance after the UK referendum on European Union membership (the so-called Brexit referendum). By using a unique survey, we found that relationship lending significantly reduces SMEs' expectations of being financially constrained, although the same does not hold for firms engaging in product innovation. Our results are robust after controlling for accounting information disclosure and for the relationship between the expectation of access to debt finance, the prospect of growth, and changes in business strategies.